Is China’s one-child policy becoming redundant? - Cestr, Ondřej; Nikolovová, Pavla, 1982-; Špecián, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
Contemporary China is facing the threat of rapidly aging population. Increasing portion of the economically inactive part of the population is already putting a significant strain on the Chinese pension system. Health care and social security system are still underdeveloped and also unprepared for this trend. As an attempt to reduce this issue by revitalizing the low birth rate, Chinese one-child policy underwent a significant relaxation in 2007. The expected acceleration of the birth rate however did not occur. Using the panel data from 31 regions of China between the period 2001 and 2013, I have analyzed this issue. My thesis provides the evidence, that one-child policy is not the exclusive culprit behind the continued trend of below-replacement fertility levels. Socioeconomic environment in China underwent a rapid transformation during the past 37 years. One of the socioeconomic factors newly affecting the Chinese birth rate level is the wealth. This is manifested by the inverse relationship between the wealth and fertility and it is known as the demographic-economic paradox. This thesis proves the presence of this phenomenon across the regions of China. It also demonstrates that it could have at least partly counterweighted the effect, which one-child policy easing had on birth rate in 2007. Since the one-child policy has lost significant part of its normative power to other factors affecting the birth rate, I am arguing it is the sign, that one-child policy is slowly becoming redundant on its own.
Vedoucí práce: Pavla Vozárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses